Strengthening institutions for public health education: results of an SWOT analysis from India to inform global best practices - Emily Miller; Megha Reddy; Preetika Banerjee; Haley Brahmbhatt; Piyusha Majumdar; D. K. Mangal; Shiv Dutt Gupta; Sanjay Zodpey; Anita Shet; Meike Schleiff (BMC, 2022)
Abstract Background Developing public health educational programs that provide workers prepared to adequately respond to health system challenges is an historical dilemma. In India, the focus on public health education has been mounting in recent years. The COVID-19 pandemic is a harbinger of the increasing complexities surrounding public health challenges and the overdue need to progress public health education around the world. This paper aims to explore strengths and challenges of public health educational institutions in India, and elucidate unique opportunities to emerge as a global leader in reform. Methods To capture the landscape of public health training in India, we initiated a web-based desk review of available offerings and categorized by key descriptors and program qualities. We then undertook a series of in-depth interviews with representatives from a purposively sample of institutions and performed a qualitative SWOT analysis. Results We found that public health education exists in many formats in India. Although Master of Public Health (MPH) and similar programs are still the most common type of public health training outside of community medicine programs, other postgraduate pathways exist including diplomas, PhDs, certificates and executive trainings. The strengths of public health education institutions include research capacities, financial accessibility, and innovation, yet there is a need to improve collaborations and harmonize training with well-defined career pathways. Growing attention to the sector, improved technologies and community engagement all hold exciting potential for public health education, while externally held misconceptions can threaten institutional efficacy and potential. Conclusions The timely need for and attention to public health education in India present a critical juncture for meaningful reform. India may also be well-situated to contextualize and scale the types of trainings needed to address complex challenges and serve as a model for other countries and the world.